2009
DOI: 10.1007/s10661-009-1185-1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of soil radioactivity levels and radiation hazard assessment in southern Rechna interfluvial region, Pakistan

Abstract: Rechna interfluvial region is one of the main regions of Punjab, Pakistan. It is the area which is lying between River Ravi and River Chenab, alluvial-filled. Radioactivity levels in soil samples, collected from southern Rechna interfluvial region, Pakistan, have been estimated by using gamma-ray spectrometric technique. (226)Ra, (232)Th, the primordial radionuclide (40)K, and the artificial radionuclide (137)Cs have been measured in the soil of the study area. The mean radioactivity levels of (226)Ra, (232)Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 20 publications
0
17
1
Order By: Relevance
“…In Absorbed dose rate (D), it is important to point out that the value obtained is higher than the world average and higher than levels reported in the United States, Switzerland, Luxemburg, Japan, Romania, Taiwan and others countries (Dolhań czuk-Ś ródka, 2012;Jabbar et al, 2010;Mehra et al, 2007;Quindos, Fernández, Rodenas, Gómez-Arozamena & Arteche, 2004;Tzortzis, Tsertos, Christofides & Chistodoclides, 2003). Similar studies carried out in other regions of Mexico have reported lower values than those in Chihuahua.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…In Absorbed dose rate (D), it is important to point out that the value obtained is higher than the world average and higher than levels reported in the United States, Switzerland, Luxemburg, Japan, Romania, Taiwan and others countries (Dolhań czuk-Ś ródka, 2012;Jabbar et al, 2010;Mehra et al, 2007;Quindos, Fernández, Rodenas, Gómez-Arozamena & Arteche, 2004;Tzortzis, Tsertos, Christofides & Chistodoclides, 2003). Similar studies carried out in other regions of Mexico have reported lower values than those in Chihuahua.…”
Section: Discussionmentioning
confidence: 66%
“…It is important to point out that Ciudad Aldama had the highest values of the three natural isotopes: 67% higher than the world average for K. Comparing the averages in Chihuahua to those in other countries we can see that it has higher NORM levels than Luxemburg, Hungary, Japan, Bangladesh, China, Romania and Spain, and similar values to regions like Punjab, India (Dolhań czuk-Ś ródka, 2012;Jabbar et al, 2010;Mehra et al, 2007). Chihuahua city and Chihuahua State have been mentioned in others papers for its high radioactive levels (Colmenero-Sujo et al, 2004;Colmenero-Sujo & Villalba, 2010;Villalba et al, 2012).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations